2022
DOI: 10.1002/app.53085
|View full text |Cite
|
Sign up to set email alerts
|

Study on the healing performance of poly(ε‐caprolactone) filled ultraviolet‐curable 3D printed cyclic trimethylolpropane formal acrylate shape memory polymers

Abstract: The research and application of ultraviolet‐curable 3D printed shape memory polymers have been focused on artificial intelligence, bionic engineering, and medical devices, and so forth. However, this photopolymer has the disadvantages of low toughness and easy to be damaged. As a healing agent and toughening agent, the thermoplastic polymer polycaprolactone (PCL) is used to improve the utility value of 3D printed cyclic trimethylolpropane formal acrylate (CTFA) shape memory composites. The filling content of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…For the latter, Zhang et al incorporated PCL into BMA/PEGDMA at 3:1 ratio and observed a reduction in mechanical strength while increasing its ductility. Wen et al observed similar behavior when PCL was blended into CTFA/TPO. In both of these cases, the matrix material had greater tensile strength but was more brittle, as compared to PCL (for example, BMA/PEGDMA had a tensile strength of approximately 30 MPa and a strain at break of 10% and CTFA with TPO had a tensile strength of approximately 40 MPa and a strain at break of 10%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the latter, Zhang et al incorporated PCL into BMA/PEGDMA at 3:1 ratio and observed a reduction in mechanical strength while increasing its ductility. Wen et al observed similar behavior when PCL was blended into CTFA/TPO. In both of these cases, the matrix material had greater tensile strength but was more brittle, as compared to PCL (for example, BMA/PEGDMA had a tensile strength of approximately 30 MPa and a strain at break of 10% and CTFA with TPO had a tensile strength of approximately 40 MPa and a strain at break of 10%).…”
Section: Resultsmentioning
confidence: 99%
“…Although this is different than the testing method we employed, it is comparable as both these test methods evaluate the adhesion strength of PCL upon healing. Wen et al 10 found that their vat-polymerized CTFA and TPO blended with PCL exhibited self-healing starting at 5 wt % PCL but were unable to produce good prints at 20 wt % PCL. Self-healing was determined based on cut tests and visual examination.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acrylate polymers demonstrate a model system for assessing SMPs' strain tolerance and have a variety of potential uses. Little compositional modifications have a considerable impact on mechanical properties when copolymerizing different acrylate monomers, including elastic modulus, strain‐to‐failure, T g , brittleness at ambient temperatures, and rate of deformation in the rubbery rule 20,17,21,22 . Its high glass transition temperature of 94°C for poly(isobornyl acrylate), or P(IBoA), and 19.6 kg/mm 2 of hardness at 20°C 23 are only two of its unique physical properties.…”
Section: Introductionmentioning
confidence: 99%